A new species of Protodorvillea (Polychaeta: Dorvilleidae) from the Western Mediterranean Sea. Issue 1 (1st January 2019) - Munari, C.; Ebbe, B.
Abstract: A new species of Dorvilleidae, Protodorvillea artemidis sp. nov., is described from the soft bottom of the Gulf of Taranto (northern Ionian Sea) and the Straits of Messina (southern Tyrrhenian Sea), in the western Mediterranean Sea. The specimens were collected in October 2014, near the village of Rossano Calabro (Southern Italy, Ionian Sea), and in July 2016 off the village of Scilla (Southern Italy, Tyrrhenian Sea), from 6 to 38 m depth. Protodorvillea artemidis sp. nov. is characterised by four eyes, two short clavate antennae, dorsal and ventral cirri from the first parapodium, a long subacicular falciger reminiscent of that of Dorvillea, and the simultaneous occurrence of supraacicular and subacicular cultriform chaetae with serrated edges. Protodorvillea artemidis sp. nov. is similar to P. kefersteini (McIntosh, 1869) but differs from this species mainly by morphological characteristics of prostomium, mouth parts, and supraacicular and subacicualar chaetae. Morphological characters important for differentiation of the new species herein described from congeneric species are discussed. The description of P. artemidis sp. nov. helps to improve the knowledge on the diversity of Mediterranean invertebrates, and specifically on the family Dorvilleidae, which is still poorly known and includes many opportunistic species, early indicators of pollution. urn:lsid:zoobank.org:pub:AC147ADF-762A-4797-A9AE-FC0BA1219D1A